2018
DOI: 10.1136/bmjopen-2018-023770
|View full text |Cite
|
Sign up to set email alerts
|

The role of osteopathy in the Swiss primary health care system: a practice review

Abstract: ObjectivesThe aim of this study was to describe osteopathic activity and scope of practice to understand the current and future role of osteopathy in the Swiss healthcare system.DesignA questionnaire survey that included a patient record-based retrospective clinical audit.Setting/populationOsteopaths with a national diploma (n=1086) were invited by mail to participate in an online survey. Osteopathic assistants (n=84) were identified through their national association.QuestionnaireThe survey was constructed fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
51
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 24 publications
(16 reference statements)
12
51
2
2
Order By: Relevance
“…The use of this diagnostic system on a consistent basis across the profession, may help to provide a more accurate picture of the breadth of conditions treated by Australian osteopaths [28]. This finding is consistent with the literature suggesting that the management of spinal complaints forms a core aspect of the practice of osteopathy in Australia and internationally [1,15,16,[18][19][20][21]. More patients presented with acute presentations of less than 3 months duration (52%) than chronic presentations.…”
Section: Patient Clinical and Demographic Profilesupporting
confidence: 77%
See 4 more Smart Citations
“…The use of this diagnostic system on a consistent basis across the profession, may help to provide a more accurate picture of the breadth of conditions treated by Australian osteopaths [28]. This finding is consistent with the literature suggesting that the management of spinal complaints forms a core aspect of the practice of osteopathy in Australia and internationally [1,15,16,[18][19][20][21]. More patients presented with acute presentations of less than 3 months duration (52%) than chronic presentations.…”
Section: Patient Clinical and Demographic Profilesupporting
confidence: 77%
“…These practice profiles utilised different methodologies, however all three studies suggested that patients sought care for complaints predominantly affecting the cervical and lumbar spine. Burke et al [1] also identified that over one-third of patient's seeking osteopathy care also present with one or more co-morbid chronic diseases and this appears to be consistent with international practice profiles [16,19]. These studies reported characteristics of osteopathic patients in private practice settings.…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations